Implementasi Layanan Kunjungan Berbasis IT untuk Pengunjung Lembaga Pemasyarakatan Kelas II A Karawang - Eko Haryadi (JURNAL REKAYASA INFORMASI, 2019)
The need to develop an application program and information system for the process of arranging the family visits of prisoners is needed in the Class II A penitentiary in Karawang. the development of this program was made with the aim of being able to provide prison officers with information in advance how many families would visit, the time and equipment carried. this program was built by creating patient data, visitor data and employee data by using waterfall methods. With the development of a program created with a web-based system and using a QR code, it can help families to meet with residents and help officials record prison visitors. Key words : application program, QR Code, application program web based